PENGEMBANGAN POTENSI UBI JALAR UNTUK KETAHANAN PANGAN KELUARGA DAN PEMANFAATAN LAHAN PEKARANGAN BAGI KELOMPOK WANITA TANI (KWT) BAYUR LESTARI BANDAR LAMPUNG (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2022)
Sweet potatoes are plants that have stem tubers. There are a variety of kinds based on the color of its tuber, such as white, yellow, and purple. The purple color in purple sweet potato is caused due to the existence of anthocyanins. Purple sweet potato was chosen because it gives health benefits to its consumer as it contains beta-carotene and anthocyanins as sources of antioxidants. Because of its benefits, it can be said that purple sweet potato is one of the food security sources for families. Thus, the cultivation of purple sweet potato is necessary and pioneered by Kelompok Wanita Tani (KWT), such as KWT Bayur Lestari by utilizing the existing yard. The plantation was done using sacks in order to minimize the used area. The aim of this activity is to increase the knowledge and skills of KWT Bayur Lestari in cultivation using the existing yard. The results of the community service program showed an increase in knowledge based on test results of 18,26 points, from 80,43 points to 98,70.